The attitudes toward early marriage among adolescents in Yogyakarta - Sri Astuti Handayani; Nanik Setiyawati; Hasan Basri Borut (Jurnal Kesehatan Ibu dan Anak, 2021)
The prevalence of early marriage in Yogyakarta increased in 2018 with a total of 312 cases. There are three districts in Yogyakarta with the highest number of cases, namely Sleman 93 cases, Gunung Kidul 77 cases, and Kulon Progo 71 cases. The purpose of this study was to know the factors related to adolescent attitudes about early marriage in Yogyakarta. The research was conducted with quantitative observational analytics with a cross-sectional design. The sampling technique used a sampling quota with several 75 respondents. Research instruments in the form of questionnaires. The data is analyzed with a chi-square test and multivariate with a logistic regression test. The results of this study showed that out of 79 respondents, 78.5% had no intention of early marriage, and 21.5% intended to have an early marriage. Based on the results of the analysis of the known knowledge variable (p=0.010, OR=4.133), parental income (p=0.016, OR=4.072) showed that there was a correlation with adolescents' intentions towards early marriage. Meanwhile, the family support variable (p=0.738), peer support (p=0.505), and attitude (p=0.105) indicate no connection with a teenager's intentions toward early marriage. The results were obtained that factors related to adolescents' intentions toward early marriage are the knowledge and income of parents.